From Isolation of Phosphate Solubilizing Microbes to Their Formulation and Use as Biofertilizers: Status and Needs - Soumare, Abdoulaye; Boubekri, Kenza; Lyamlouli, Karim; Hafidi, Mohamed; Ouhdouch, Yedir; Kouisni, Lamfeddal (Frontiers in Bioengineering and Biotechnology, 2020)
The production of biofertilizers at industrial level is a bottleneck because bacterial strains are generally developed and managed by research laboratories and not by production units. A seamless transition from laboratory to field application is, therefore necessary. This review provides an overview of the constraints that limiting the application or the implementation of Actinobacteria based biofertilizers especially in agricultural field and suggests solutions to overcome some of these limits. General processes of making and controlling the quality of the inoculum are briefly described. In addition, the paper underlines the opportunity of biofertilizers alone or in combination with chemical fertilizers. This review also, highlights the latest studies (until June 2019) and focuses on P-solubilization microorganisms mainly Actinobacteria. The biotechnology of these bacteria is a glimmer of hope for rock phosphate (RP) bioformulation. Since direct application of RP fertilizer is not always agronomically effective due to its sparse solubility.